Mental Health Effects of Premigration Trauma and Postmigration Discrimination on Refugee Youth in Canada. Issue 6 (June 2016) - Beiser, Morton; Hou, Feng
Abstract : Abstract: This report examines the role of pre- and post-migration trauma in explaining differences in refugee and immigrant mental health. Data were derived from mother-youth refugee and immigrant dyads from six countries of origin who were living in Canada at the time of the study. Youth reports of emotional problems (EP) and aggressive behavior (AB) were the mental health outcomes. EP and AB were regressed on predictor blocks: a) status (refugee versus immigrant), visible minority, and gender; b) premigration trauma and postmigration discrimination; c) parent and youth human and social capital; d) poverty, neighborhood, and schools. Refugees suffered higher levels of EP and AB, premigration traumas, and discrimination. Postmigration perception of discrimination predicted both EP and AB and explained immigrant versus refugee differences in EP. Antirefugee discrimination net of discrimination based on immigrant or visible minority status has deleterious mental health consequences.